Early intervention in thyroidectomy scars: demographics, symptoms, and prevention. - J.U. Shin; J.H. Park; S.H. Oh; J.J. Jeong; S. Kang; K. Nam; W.Y. Chung; J.H. Lee (Journal of Wound Care, 2015)
l Objective: Although hypertrophic scars are cosmetically problematic for patients following thyroidectomy, the associated risk factors are not well defined. Our objective was to determine the factors associated with hypertrophic scar development following thyroidectomy. l Method: A retrospective chart review was performed collecting data on sex, age, body mass index (BMI), operation site, skin characteristics (pigmentation, erythema, elasticity, and hydration), and clinical scar characteristics (itching, tightening, induration, adhesion, and oedema). It was also noted if the patient had early scar intervention with intralesional steroid injection or non-ablative fractional laser irradiation, and preventive topical treatment agents. The effects of these factors were analysed using univariate and multivariate analyses. l Results: Data from 1141 patients showed the incidence of hypertrophic scars was 13.9%. Significant variables in univariate analysis were combined for multivariate analysis. Young age, high BMI, itching, tightening, induration, and adhesion were associated with hypertrophic scar formation. Early scar intervention, as well as the use of preventive topical agents, were associated with decreased hypertrophic scar formation. l Conclusion: Based on our results, we suggest that dermatologists consider using non-ablative fractional laser, intralesional steroid injection, and topical preventive agents to lower the incidence of hypertrophic scars, especially in young patients or those with high BMI and/or clinical symptoms such as itching, tightening, induration, and adhesion. l Declaration of interest: The authors have no proprietary or commercial interest in any materials discussed in this article. The authors have no conflict of interest. This study was supported by a faculty research grant of Yonsei University College of Medicine for 2007 (6-2007-0142). This research was also supported by the Basic Science Research Program through the National Research Foundation of Korea (NRF) funded by the Ministry of Education, Science, and Technology (7-2010-0285, 7-2011-0203).